Working around inadequate information systems in the workplace: An empirical study in Romania. (June 2022) - Wong, Louie H.M.; Hurbean, Luminita; Davison, Robert M.; Ou, Carol XJ; Muntean, Mihaela
Abstract: We explore how employees behave when faced with information systems (IS) that inadequately support their work. Inadequate IS often induce workaround behaviour, a phenomenon that is insufficiently understood in contemporary organisations. Drawing on workaround theory and coping theory, we develop a research model that links inadequate IS with corporate policy and employee attitudes to workaround behaviour. We test the model with data collected from 310 employees of Romanian organizations who currently use enterprise systems. We discuss the implications of the study for practice and research, as well as future directions and theoretical possibilities. Highlights: Inadequate information systems cause problems for employees. Employees who face inadequate information systems may create workarounds. We test a model of workarounds with data from 310 respondents. We identify factors that influence workaround behaviour. Managers need to consider how workarounds benefit the organisation.